Dimensions of global economic restructuring and the idea of decentralising labour relations in Australia - Clark, G (Blackwell Publishing, 1991)
Though always more exposed than many other countries to the vicissitudes of international competition, Australia seems to have become increasingly vulnerable to the pressures accompanying global restructuring. This much is evident in the pattern of foreign debt, the balance of payments and trade, and fluctuations in our exchange rate. Media paranoia over the day-to-day pegormance of macro-indicators obscures, however, the pressures global restructuring has brought against the integrity and efficacy of our major institutions Not only have there been serious questions raised about the usefulness of the centralised arbitration system in the context of global restructuring, the Australian labour movement itself faces an uncertain future. Notwithstanding the claimed virtues of an enterprise-based labour relations system, there are good reasons to suppose that a decentralised system would have its own problems in accommodating rapid economic change. In this respect, the search for an American-style decentralised institutional regime may be ill-advised; more useful may be an enhanced capacity to adjust within the current framework of Australian labour relations.